Effects of water and feed based RISCO-NUTRIFOUR probiotic supplementation on the technological and physicochemical quality of broiler breast meat - Al-abdullatif, Abdulaziz A.; Al-Garadi, Maged A.; Qaid, Mohammed M.; Matar, Abdulkareem M.; Alobre, Mohsen M.; Al-Badwi, Mohammed A.; Hussein, Elsayed O.; Suliman, Gamaleldin M. (Frontiers in Veterinary Science, 2025)
IntroductionConsumer interest in poultry and high-quality meat products has increased. Probiotics are used in the diet to improve the quality of broiler meat. The aim of this study was to investigate the effects of multi-strain probiotics (RISCO-NUTRIFOUR®, RNF) on the quality and physicochemical properties of broiler meat.MethodsA total of 288 broilers received six feed treatments for 1-14 days in water and 15-28 days in feed. T1-T3 received 0.4%, 0.2%, and 0.1% RNF, respectively; T4 received 0.1% Bacillus subtilis (BS; CLOSTAT®); T5 received 0.1% Saccharomyces cerevisiae (SC); and T6 received 0.0% probiotic (NC). The meat quality and physicochemical properties of the broiler breast were evaluated on day 28.Results and discussionRNF, especially at 0.1% RNF, significantly reduced cooking losses was more tender (required the least SF), and improved average body weight at day 28 and total numerical feed conversion ratio compared to controls. The RNF probiotic had a positive effect on the texture profile (especially 0.4% RNF), sensory properties, and body weight (especially at 0.2% RNF). In conclusion, 0.4% RNF is recommended to achieve the best texture profile, 0.2% RNF to achieve the best juiciness and overall sensory acceptability as well as the best target weight of the broilers, and 0.1% RNF to achieve the most tender texture and the lowest cooking losses at day 28 compared to the controls.